UTILIZING ECOBRICKS AS LEARNING MEDIA FOR STUDENTS WITH INTELLECTUAL DISABILITIES - Lukman, Imam Abdillah; Ulfa, Maria; Siregar, Muhammad Filhal Haqqani (Universitas Muhammadiyah Aceh, 2024)
PThis Community Service Project aims to enhance environmental awareness and practical skills among students with special needs, particularly those with intellectual disabilities. By introducing the concept of ecobricks, a sustainable way to recycle plastic waste, this project seeks to empower students and foster a sense of environmental responsibility. The project is implemented at SLB Bukesra Uleekareng, where workshops are conducted to teach students and teachers the process of making ecobricks from recycled plastic. Through hands-on activities, participants learn about the environmental impact of plastic pollution and the importance of waste reduction. The project also focuses on developing students' fine motor skills, creativity, and problem-solving abilities. To ensure the project's sustainability, a comprehensive guidebook is developed to serve as a resource for teachers and students. This guidebook provides detailed instructions on making ecobricks and suggests various ways to incorporate them into the classroom. The project successfully demonstrates the potential of ecobricks as an innovative teaching tool and a practical solution to plastic waste. Keywords: Ecobricks, SLB, Mentally Disabled